Design and Performance Evaluation of a Secure and Energy-Efficient Cloud-Based Architecture for Wireless Sensor Networks (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The current IoT and its uses rely heavily on Wireless Sensor Networks (WSNs) and knowledge on how to get data from them in real time. Many fields can greatly benefit from WSNs, including healthcare, smart cities, environmental monitoring, industrial automation, and many more. Energy, security, scalability, and data management are only a few of the major limiting variables that affect WSNs, which are extensively used structures. Unfortunately, WSNs have a lot of problems when it comes to data management, security, scalability, and energy storage. There are potential ways to keep their efficiency and energy consumption low, and WSNs and cloud computing integrations can assist with this. In this article, we will go over the latest advancements in Wireless Sensor Networks (WSNs) and how they are being used to WSNs in cloud environments and frameworks. The goal is to increase and sustain efficiency while minimizing costs associated with communication, energy, and security. We will go over the latest innovations in Wireless Sensor Networks (WSNs), including WSNs in clouds and frameworks, as well as WSNs themselves, in order to keep efficiency high, reduce energy and communication costs, and increase security. To alleviate storage and processing constraints, the components of the WSN are required to pay for cloud tools that each component can use. Consequently, the proposed adapters are more difficult and expensive to implement on the Adapter. Traditional WSN methods are evaluated and contrasted with metrics such energy consumption, end-to-end latency, throughput, packet delivery ratio, detection accuracy, and network longevity. Energy efficiency, dependability, security, and scalability are all well exhibited in the results. In addition to being suitable for next-generation IoT and data-intensive applications, the suggested architecture can handle the demands of massive cloud-based WSN installations.